Pathological processes in aqueous humor due to iris atrophy predispose to early corneal graft failure in humans and mice - Yamaguchi, Takefumi (Sci Adv, 2020)
Corneal endothelial cell (CEnC) loss after corneal transplantation is the major cause of graft failure and remains a clinically relevant challenge to overcome. Accumulated knowledge derived from long-term clinical outcomes suggested that elevated protein levels in the aqueous humor are associated with CEnC loss. However, the full spectrum of driver proteins and molecular processes remains to be determined. Here, we defined the somatic microenvironmental landscape and cellular response across human aqueous humor in samples with poor corneal transplantation clinical outcomes using multiomics analyses and clarified specific driver alterations, including complement activation and disturbed energy homeostasis. These driver alterations were also confirmed in aqueous humor from a novel murine model that spontaneously develops iris atrophy, leading to CEnC loss. The application of the integrative multiomics performed in human samples to the novel murine model will help the development of therapeutic modalities for patients with CEnC loss after corneal transplantation.